Management of Artisanal Fishing Port: a case study on Labuhanhaji fishing port, South Aceh Regency, Aceh Province - NurJannah, Betri; Zain, Jonny; ', Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A series survey activity was carried out for evaluating management function atlabuanhaji fishing port, South Aceh regency. This research was emphasis on planning, organizing, action and controlling at management pattern of labuhanhaji fishing port. The facilities of fishing port data and daily activities description of staff at labuhanhaji fishing port was used as additional information and consideration in management of labuhanhaji fishing port. Lack of good management was impact on staff and controlling, nevertheless activities at labuhanhaji fishing port is going well.Keywords: Labuhanhaji fishing port, management, South Aceh Regency